The use of stereological methods in the histomorphometric assessment of bone for age-at-death estimation. (September 2018) - Botha, D.; Bhagwandin, A.; Lynnerup, N.; Steyn, M.
Abstract: Stereological examination of the anterior femur was done for the estimation of age-at-death. The aim of this study was to assess particular bone microstructures that change with advancing age and use these variables to create revised regression formulae applicable to the black population of South Africa. A sample of 99 bone sections (n = 60 males and n = 39 females) that had previously been analysed using 2D methods, were re-analysed using the optical fractionator and nucleator sampling methods. Single and multiple regression analyses were performed to assess the strength of the relationship between known age and all independent variables. For sex-pooled data, the average number of osteons per grid area (Avg_OPD) showed the highest correlation with age (r = 0.528; r 2 = 0.278), followed by average osteon volume (r = −0.383; r 2 = 0.146). The remaining variables reflected a low correlation with age. Pooled, as well as sex-specific single regression formulae were constructed. Multiple regression formulae were constructed for pooled sexes only, as there were no significant difference between males and females overall. Although the employment of stereological methods ensured that the results are accurate and unbiased, the outcome was on par with previously reported SEE's and SD's for this population.